STUDI KASUS POLA PEMBERIAN REMUNERASI RESIDEN DI RSUD DR. MOEWARDI SURAKARTA - Sudirman; Laksono Trisnantoro; Andreasta Meliala (Jurnal Manajemen Pelayanan Kesehatan (The Indonesian Journal of Health Service Management), 2021)
Background: Since the commencement of the national healthinsurance program (JKN), patient visits to hospitals haveincreased. The same is true for patient referrals with specialistcases. The limited ability of specialist doctors in dealing with theincreasing number of specialized cases has made hospitalsstart considering resident personnel to help provide medicalservices, especially in teaching hospitals. The magnitude of theresident's role in providing medical services in teachinghospitals needs serious attention, especially in relation to theresident's right to receive remuneration for medical servicescarried out in accordance with the mandate of Law Number 20 of2013 concerning medical education.Objectives: This study aimed to evaluate the policy of providingremuneration or incentives for residents who provide medicalservices at Dr. Moewardi Surakarta.Methods: This study is a non-experimental study with adescriptive case study design with a single holistic case design.The research was conducted at Dr. Moewardi and FK UNSduring January–February 2016 with 10 respondents asresearch subjects and carried out by purposive samplingmethod.Results: Remuneration for residents that has been applied inDr. Moewardi was very dependent on the university-basedsystem applied by FK UNS in organizing specialist medicaleducation programs. Resident remuneration that has beengiven only includes incentives and does not refer to LawNumber 20 of 2013 concerning medical education whichregulates resident incentives. The provision of residentincentives has the same pattern regardless of the type ofspecialization and level of competence.Conclusions: The pattern of incentives that have beenimplemented by RSUD Dr. Moewardi does not difffferentiateincentives based on the type of specialization or level ofcompetence and is not in accordance with Law Number 20 of2013 concerning medical education.